2021
DOI: 10.1021/jacs.1c01525
|View full text |Cite
|
Sign up to set email alerts
|

Short-Range Ordered Iridium Single Atoms Integrated into Cobalt Oxide Spinel Structure for Highly Efficient Electrocatalytic Water Oxidation

Abstract: Noble metals manifest themselves with unique electronic structures and irreplaceable activity toward a wide range of catalytic applications but are unfortunately restricted by limited choice of geometric structures spanning single atoms, clusters, nanoparticles, and bulk crystals. Herein, we propose how to overcome this limitation by integrating noble metal atoms into the lattice of transition metal oxides to create a new type of hybrid structure. This study shows that iridium single atoms can be accommodated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
297
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(328 citation statements)
references
References 48 publications
8
297
0
Order By: Relevance
“…reported that Ir single atoms can be accommodated into the cationic sites of cobalt spinel oxide with short‐range order and an identical spatial correlation as the host lattice. [ 139 ] In particular, due to the strong interaction between Ir and cobalt oxide support, the resultant Ir 0.06 Co 2.94 O 4 exhibits remarkable operational stability under OER condition. Thus, the rational design of long‐range ordering (with crystalline structure), short‐range ordering (with amorphous structure) and crystalline‐amorphous materials needs more insights into the material properties and in‐depth understanding of the structure‐activity relationship.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…reported that Ir single atoms can be accommodated into the cationic sites of cobalt spinel oxide with short‐range order and an identical spatial correlation as the host lattice. [ 139 ] In particular, due to the strong interaction between Ir and cobalt oxide support, the resultant Ir 0.06 Co 2.94 O 4 exhibits remarkable operational stability under OER condition. Thus, the rational design of long‐range ordering (with crystalline structure), short‐range ordering (with amorphous structure) and crystalline‐amorphous materials needs more insights into the material properties and in‐depth understanding of the structure‐activity relationship.…”
Section: Summary and Perspectivementioning
confidence: 99%
“…Studies have shown that Ir single atom can enter the cation center of the cobalt spinel oxide in a short‐range orderly manner, and there is a spatial correlation with the oxide crystal lattice. [ 134 ] Among the prepared series of Ir x Co 3– x O 4 ( x = 0.003, 0.01, 0.04, 0.06, and 0.16) catalysts, Ir 0.06 Co 2.94 O 4 showed the best performance. Under acidic conditions, the electrocatalytic activity of the synthesized Ir 0.06 Co 2.94 O 4 catalyst for OER is two orders of magnitude higher than that of Co 3 O 4 .…”
Section: Electrocatalysts For Acidic Oermentioning
confidence: 99%
“…Through in situ and semi in situ tests, it is found that this is due to the strong interaction between Ir and the cobalt oxide support. [ 134 ] In conclusion, the strong interaction between the support and the metal atoms enhances the stability of the active site, which is important for solving the solubility of nanocrystalline catalysts in acidic OER.…”
Section: Electrocatalysts For Acidic Oermentioning
confidence: 99%
“…[3] Up to now, although numerous transition metal-based electrocatalysts with earth-abundance reserves have been extensively studied while getting important progress, [4] Pt-group metal (PGM) electrocatalysts with unique electronic structures and irreplaceable comprehensive performance still play a crucial role in the field of electrocatalysis. [5] Nevertheless, the commercial viability of PGMs suffers from their poor stability, high cost and scarcity. To this end, increasing electrocatalytic activity and stability while reducing the amount of noble metals has always been a key issue in the scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…filling. [5,19] The anions embracing B, P, S, Se etc. possess high flexibility in modulating the local electronic structures and surface adsorption properties, providing a promising prospect for the further development of advanced electrocatalysts with better performance and lower noble metal loading.…”
Section: Introductionmentioning
confidence: 99%